The truth about personal finance : collections. - Weisman, Steve; Weisman, Steve; Bell, S. Kay; Weisman, Steve (Truth about (FT Press), 2011)
"Three full books of proven solutions for building wealth and safeguarding your retirement! Use IRAs and 401(k)s to save more and pay lower taxes ... maximize all your legal tax deductions and credits ... avoid costly retirement investing pitfalls ... protect yourself against phishing, pharming, slamming, and other scams ... and much more!"--Resource description page.